Bridging Tradition and Technology: A Hybrid Model for Qur'anic Learning in the Digital Age - Akh Syaiful Rijal; Bina Prima Panggayuh; A. F. Mawardi Sufyan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Qur’an teaching methods have shifted from traditional face-to-face talaqqi-musyafahah to digital systems. While previous studies focused on technical efficiency, few examined how digital media affects sanad continuity, student etiquette (adab), and teacher-student spiritual relationships. This study aims to map this transformation, analyze digital integration challenges, and formulate a hybrid pedagogical model for Qur’an instruction. A qualitative case study was conducted at SDI Al-Barokah, Pamekasan, from February to April 2026. Primary data were gathered with semi-structured interviews with 4 certified teachers and 12 students, observations, and documentation. Data were analyzed using the Miles and Huberman model, validated through triangulation and member-checking. The research reveals three main findings. First, the transformation evolved across three phases: traditional talaqqi-musyafahah, modern-classical modular, and hybrid-digital. Second, digital integration presents three major challenges: reduced tajwid accuracy, weakened adab, and a strained teacher-student bond. Third, the study introduces the Hybrid Talaqqi Framework to bridge traditional methods and digitalization. In this model, technology serves as a self-directed learning tool, while face-to-face sessions remain essential for validating recitation and instilling character. A structured blend of in-person and digital elements is crucial for preserving sanad continuity while leveraging technological flexibility. Practically, this study proposes a curriculum framework with a 60:40 ratio based on the Hybrid Talaqqi Framework for Islamic schools undergoing similar digital transformations.